Knowledge, attitudes, and practices of secondary school students towards COVID-19 in Sana'a City, Yemen: A cross-sectional study - Al-Shahethi, Ahmed H.; Alhidary, Ahmed; Alrubaiee, Gamil Ghaleb; Al-Shahethi, Hakim M.; Al-Shameri, Emad A.; Abol Gaith, Fawz Mohammad; Al-Dhahari, Amar Ali; Al-Soofi, Ahmed Mohammed; Abkar, Mohammed Abdo; Al-Surimi, Khaled (SAGE Publications, 2018)
Background: Understanding of public awareness on public health issues is very crucial, including the current health crisis of COVID-19. This research aimed to examine the Knowledge, Attitudes and Practices among Students towards COVID-19. Design and methods: A cross-sectional survey was conducted among secondary school students in grades 10-12. Proportional sample allocation was used in 16 randomly selected schools. Moreover, the schools were recruited by using a systematic random sampling technique. Socio-demographic data and questions of the knowledge, attitude and practice were collected by interview. Logistic regression analyses were employed to identify the associated factors and p-value?<?0.05 was considered statistically significant. Results: Among the 357 participants the level of good knowledge, positive attitude, and optimal practice were 65.2%, 66.7% and 89.4% respectively. Regression analyses showed that being in the adolescent age group (15-16?years old), living with >5 family size, and family with a good income effectively predicted knowledge level. Attitudes towards COVID-19, male students were pessimistic about COVID-19 prevention and control measures as opposed to their female counterparts [aOR?=?0.39; 95% CI: 0.21-0.71). Students with awareness of the virus demonstrated greater (two-fold) odds of a positive attitude as opposed to their less-conscious counterparts. The urban-area male students were demonstrated a higher (three-fold) odds of good practice level towards COVID-19 prevention and control measures as opposed to their rural-area female counterparts. Conclusion: A good knowledge level denoted a positive attitude despite the lack of information. Meanwhile, good preventive measure practices and behaviours reflected high levels.